Rice and green gram based ‘Tempeh’- Development and in vitro mineral bioavailability - Lakshmy, P.S.; Usha, V.; Sharon, C.L.; Aneena, E.R. (Journal of Tropical Agriculture, 2016)
Fermentation is one of the household food technologies by which the nutritive value of foods could be improved. ‘Tempeh’ is one of the most widely accepted and researched mould modified fermented product. Tempeh is traditionally made with soybeans only. In Indian situation where a variety of cereals and pulses are used, tempeh could be prepared with these. Hence,in the present study, tempeh types were standardised using different combinations of rice and green gram and their mineral content and in vitro mineral bioavailability was assessed. Tempeh developed with 100 per cent green gram had the best texture and firmness and was comparable with the control (100 % soybean). The tempeh types showed a reduction in the total calcium, iron, phosphorus, potassium and zinc when compared to the mineral content in the raw grains used for tempeh preparation. Mineral availability studies revealed that the availability of minerals from T1 (soybean 100%) tempeh was the lowest and the highest availability of minerals was from T4 (green gram 50% + rice 50%) tempeh. The mineral bioavailability ranged from 49 to 88.99 per cent among the treatments. The availability of zinc was found to be the highest among the minerals studied.